Okiem odbiorcy: obrazy naoczne i wyobrażone. Album Echoes Shades Piotra Zbierskiego - Zarychta, Anna Maria (Załącznik Kulturoznawczy, 2020)
This essay is a proposal of such an interpretation of an artistic project that constantly balances on the border of meanings arising, in this case, from the relationship (or even tensions) between the content, form and arrangement of photographs. Viewing the album is treated here as a task immersed in both scientific reflection and – referring to Carl Gustaw Jung – as experiencing (also that which escapes rationality) and feeling, as Mircea Eliade would say, as a pre-reflection grasp, and in addition, as Kantian Ehrfahrung also immersed in memory structures. Entering the ground of discursive spaces, related, among others to anthropology as well as symbolic reflection arising from the reception of the works of Jung and Eliade, is here above all, an impulse for analysis, one of the spaces for asking questions, expanding contexts and following one’s own paths of associations and emotions, inevitably, dependent on both a professional and emotional view. The photographs gathered in the album entitled Echoes Shades (2020), taken over the past five years, illustrate the author’s ‘mystical’ journey – his search for a ‘common magical thinking’ this time in the African Omo Valley, Indonesian region of Tana Toraja.